L' empire du sultan le monde Ottoman dans l'art de la Renaissance ; [ce catalogue a été publié à l'occasion de l'Exposition L'Empire du Sultan: le Monde Ottoman dans l'Art de la Renaissance, BOZAR, Palais des Beaux-Arts, Bruxelles, du 27 février au 31 mai 2015 ; Ottomania: the Ottoman Orient in Renaissance Art, Musée National à Cracovie du 26 juin au 27 septembre 2015] - Born, Robert 1966-; Dziewulski, Michał 1978-; Messling, Guido (Lannoo, 2015)
News of the fall of Constantinople on May 29, 1453, spread throughout Europe like wildfire. The geographic approach of the Ottoman Empire coincided with the emergence of a fascination with this highly developed culture and its groundbreaking scientific insight. Artists from every corner of Europe traveled to the shores of the Bosporus; trade flourished, as did cultural interchange, giving rise to a great number of works of art that reflect this intercultural dynamism. The opulent volume presents selected examples of this early enthusiasm for the Orient and illustrates the allure that the Near East exercised on Western artists, drawing attention to the influence of the Islamic world on Renaissance thought. Masterpieces by Giovanni Bellini, Vittore Carpaccio, Albrecht Dürer, Titian, and other artists adorn this elaborate publication. Exhibition: Palais des Beaux-Arts, Brussels, Beligum (27.2.-31.5.2015).
Keywords: Geschichte 1450-1600; Kulturaustausch; Türken -- Motiv; Kultur; Rezeption; Renaissance; Kunst; Europa; Osmanisches Reich; Ausstellungskatalog -- Muzeum Narodowe w Krakowie -- 26.06.2015-27.09.2015 -- Krakau; Ausstellungskatalog -- Palais des Beaux-Arts -- 27.02.2015-31.05.2015 -- Brüssel